Novel design of a legged mobile lander for extraterrestrial planet exploration. (12th December 2017) - Lin, Rongfu; Guo, Weizhong; Li, Meng; Hu, Yuan; Han, Youcheng
During extraterrestrial planet exploration programs, the existing exploratory mode has some limitations, such as the exploratory range of the rover is limited. In this article, a concept of a novel legged robot is introduced which has inbuilt the features of lander and rover, including landing and walking capabilities as well as being deployable, orientation adjusted, and terrain adaptable. Furthermore, the rover can also be launched and work together with the robot to extend the exploratory range, and the legged mobile lander plays the role of base camp. The concept and features of the proposed robot are outlined in three stages. Firstly, the motion characteristics of the novel legged robot mapping its functions are extracted, which can be divided into global and local motion characteristics. Secondly, the structures of legs are designed according to the extracted motion characteristics, mainly composed of upper and lower parts. Thirdly, numerous structures of legged mobile landers are obtained and presented by assembling the same or different structures of legs. The number of overconstraints is selected as the qualitative index to evaluate the mechanisms. Finally, the five functions of the novel robot mentioned above are verified through taking a typical example by simulation in a software.